Jejak Gelar Doctor Honoris Causa Soekarno dan Pembelajaran Sejarah - Kurniawan, Dadan Adi; Oktavian Mahardi, Nasta Ayundra (Universitas Hamzanwadi, 2024)
Soekarno is one of Indonesia's great figures who is paradoxical, on the one hand he is widely revered but on the other hand he is also widely criticized. The traces of his life are complete, apart from receiving a lot of criticism, he also received a lot of awards. This research aims to trace the path of Soekarno's award of the doctorate honoris causa, the background factors, and how it relates to history learning. This research uses a historical method which includes five stages, namely topic determination, heuristics, criticism, interpretation and historiography. Data collection techniques use document and literature studies such as speech manuscript archives, ministerial decrees, books, journals, articles and online newspaper media. The results of the research show that Sukarno was the Indonesian president who received the most doctor honoris causa degrees, namely 26 degrees (7 awards from within the country and 19 from abroad). Awards cover the fields of law, politics, philosophy, history, social, engineering and religion. The awarding of this honorary title cannot be separated from Soekarno's great role and his political relations in the national and international arena. Historiography regarding the track record of Soekarno's doctor honoris causa degree could be a new alternative to enrich history learning material at high school and college levels.